2002
DOI: 10.1097/00006676-200201000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition and Differentiation of Pancreatic Cancer Cell Lines by PPARγ Ligand Troglitazone

Abstract: Troglitazone had growth inhibitory and differentiation induction effects on the pancreatic cancer cell lines through the upregulation of p21 expression, suggesting that ligand activation of PPAR gamma is a new molecular target for effective therapy against pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…The expression of PPAR␥ and the effect of PPAR␥ ligands on cell growth inhibition and apoptosis have been investigated in many cells including lung carcinoma (21,(23)(24)(25)(26). Although these studies showed that several PPAR␥ ligands can induce cell growth inhibition and apoptosis, little is known about the mechanism(s) mediating these effects on human lung carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of PPAR␥ and the effect of PPAR␥ ligands on cell growth inhibition and apoptosis have been investigated in many cells including lung carcinoma (21,(23)(24)(25)(26). Although these studies showed that several PPAR␥ ligands can induce cell growth inhibition and apoptosis, little is known about the mechanism(s) mediating these effects on human lung carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of growth inhibition of carcinoma cells by PPAR␥ ligands is not known, it has been shown to be associated with alterations in the expression of the cell cyclin-dependent kinase inhibitor p21 (26,27). Consistent with this idea, we showed that PGJ2 and Cig up-regulated the expression of p21 protein and mRNA concomitant with inhibition of cyclin D1 protein and mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The PPAR␥ ligand-mediated induction of p21 WAF1/Cip1 at both the mRNA level and the protein level has previously been demonstrated in other proliferationinhibition experiments using various cell types. 12,13,32,33 It is known that functional p21 WAF1/Cip1 is localized to the nucleus. 34,35 In our previous study, the nuclear localization of p21 WAF1/Cip1 was found in the PPAR␥ ligand- treated human hepatoma cells, suggesting that the liganddependent newly synthesized p21 WAF1/Cip1 was functional.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with the suggestion that PPARg acts as a tumor suppressor gene (Nakajima et al, 2001;Smith et al, 2001;Koeffler, 2003). Mechanisms of PPARg-mediated antitumor activity by Tzds demonstrated experimentally include induction of cellular differentiation (Elstner et al, 1998;Guan et al, 1999;Kitamura et al, 1999;Chang and Szabo, 2002;Kawa et al, 2002), promotion of cell cycle arrest (Brockman et al, 1998;Kitamura et al, 1999;Motomura et al, 2000;Itami et al, 2001;Koga et al, 2001;Nakashiro et al, 2001;Takashima et al, 2001;Yin et al, 2001;Kawa et al, 2002;Hong et al, 2004;Rumi et al, 2004;Chen and Harrison, 2005), antiangiogenic effects (reviewed in Alarcon de la Lastra et al, 2004) and induction of apoptosis (Elstner et al, 1998;Kubota et al, 1998;Chang and Szabo, 2000;Tsubouchi et al, 2000;Eibl et al, 2001;Takashima et al, 2001;Yang and Frucht, 2001;Lovekamp-Swan and Chaffin, 2005;Yuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%